Saving the Endangered Native Victoria Tilapia, Oreochromis Variabilis Boulenger (1906), in Upper Victoria Nile - Bassa, Samuel; Ogello, Erick Ochieng; Musinguzi, Laban; Sekiranda, Stephen; Nakiyende, Herbert (Uganda Journal of Agricultural Sciences, 2020)
This study investigated the catch estimates, mortality, growth, food and feeding habits, and water parameters of Oreochromis variabilis in Upper Victoria Nile (UVN) from 2008 to 2019. Catch rates ranged 0.32±0.08 to 3.42±1.13 kg, boat-1 , day-1 with the length-weight relationship indicating Isometric growth. Growth parameters obtained were L∞=36.75, K=0.44 yr-1 , t0=-0.4540, tmax=6.4years, ØL=2.774, ØW=-0.301. Total mortality (Z) was 1.74yr-1, natural mortality (M) =0.95yr-1 using riverine surface temperature (RST) of 26oC giving a fishing mortality F of 0.79 yr-1 and exploitation ratio (E) of 0.4504 showing that growth parameters concurs with annual estimates and yield (F=6.589; P±=0.05). Catch estimates correlated with water parameters that indicated a significant difference. Mortality parameters showed that the fishery could be experiencing exploitation pressure. Although growth rates revealed that the fish is a long-lived species, if managed properly, its population could recover. Therefore, culturing the species and restocking in rivers and lakes in which this specie was not observed in the East African region are recommended.
Keywords: Endangered species, Asymptotic values, Mortality rates, Conservation.